Holistic education in Malaysia. - Ismail, Habsah; Hassan, Aminuddin (EuroJournals, 2009)
This article discusses the concept of holistic education in Malaysia in the light of the principles adhered by the National Philosophy of Education (NPE) in the country with its focus on the development of well-balanced and integrated individuals who hold a firm belief in and devotion to God. In addressing the importance of the holistic notion of education, the Western concept of holism and integrated education as seen from the aspects of aim, philosophical principles underpinning the practices, curriculum and the teaching and learning process are also discussed. In highlighting the meaning of holistic education in Malaysia, similarities and differences in the meaning and principles of holistic education in the country and her western counterpart had been explained and the rational for the implementation of the holistic concept was provided.